Case Report: Four Early Recurrent Basilar Artery Occlusions Successfully Treated With Mechanical Thrombectomy and Subsequent Vertebral Artery Coil Occlusion - Leber, Stefan L.; Fandler-Höfler, Simon; Kneihsl, Markus; Augustin, Michael; Deutschmann, Hannes; Gattringer, Thomas (Frontiers in Neurology, 2021)
We present the case of a middle-aged patient who had four recurrent acute basilar artery occlusions over a period of three months, each time successfully treated with mechanical thrombectomy. Extensive stroke work-up showed no obvious stroke etiology aside from a hypoplastic right vertebral artery with multifocal stenoses. Treatment with different antiplatelet and anticoagulant regimes did not prevent basilar artery occlusion recurrence. Therefore, transarterial coil-occlusion of the V4-segment of the right vertebral artery was performed as ultima ratio without complications. At final discharge, the patient had no persistent neurological deficits. No further cerebrovascular events occurred over a twelve-month follow-up period.